PENGARUH KEPERCAYAAN MEREK, CITRA MEREK, DAN PERSEPSI KUALITAS TERHADAP LOYALITAS PELANGGAN MOTOR YAMAHA NMAX DI KECAMATAN GADING CEMPAKA KOTA BENGKULU - Tisa Pratiwi; Subandrio Subandrio ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study aims to determine the effect of brand trust, brand image, and perceived quality on customer loyalty for Yamaha NMax motorcycles in Gading Cempaka District Bengkulu City, either partially or simultaneously. There are several factors that will be discussed in this study, including Brand Trust, Brand Image, and Perceived Quality. The objects in this study were 60 Yamaha NMax customers in Gading Cempaka District Bengkulu City. In this research, the author uses data collection methods by means of observation, distributing questionnaires or questionnaires and interviews. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of the tests that have been carried out, it can be concluded that the variables of Brand Trust, Brand Image, and Quality Perception have partial or simultaneous effect on Customer Loyalty of Yamaha NMax Motorcycles in Gading Cempaka District Bengkulu City. From the results of multiple linear regression, the regression equation is as follows: Y = 0.398 + 0.945 () + 0.330 (X2) + 0.315 (X3). Keywords: Brand Trust, Brand Image, Perceived Quality and Customer Loyalty